Evolution of the Principle of International Responsibility to Protect (R2P) Civilians in International Law - Al- Anzi, Abdul-Salam Housain (Journal of Ecohumanism, 2024)
The application of the principle of the responsibility to protect (R2P) civilians has not helped to consolidate this principle to the extent that it has contributed to surrounding it with flaws and to the formation of additional contentious material that has contributed to renewed debate over the feasibility and legitimacy of the use of force on humanitarian basses. Whilst the adoption of a new principle entitled "Responsible Sovereignty" that presupposes a balance between sovereignty and intervention, and after benefiting from the expansion of the concept of threat to international peace and security and the elaboration of a conditional controls that must be respected, for the use of force for humanitarian motives derived from the theory of just war, the international practice of this principle has not lived up to the level of ambitions, as the dilemma of selectivity and the exploitation of intervention as a pretext by the major powers remained unresolved.